2020
DOI: 10.1111/jvim.15852
|View full text |Cite
|
Sign up to set email alerts
|

Autologous cancer cell vaccination, adoptiveT‐cell transfer, and interleukin‐2 administration results in long‐term survival for companion dogs with osteosarcoma

Abstract: Background: Osteosarcoma (OSA) in dogs is an aggressive bone tumor with frequent chemotherapy failure and translational relevance for human health. Hypothesis/Objectives: We hypothesized that dogs with OSA could be treated safely by ex vivo activated T-cells that were generated by autologous cancer vaccination and supported by interleukin-2 (IL-2) treatment with survival more than twice that reported for amputation alone. Animals: Osteosarcoma-bearing dogs (n = 14) were enrolled in a single-arm prospective tri… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 26 publications
(21 citation statements)
references
References 55 publications
0
18
0
Order By: Relevance
“…Those are then ex vivo activated (using a proprietary formula) and expanded. The cell preparation is sent back to the veterinarian for infusion ( 11 ). An update on the study results were recently presented (Bryan, 2020, personal communication) 1 , and if the data hold, this could present a treatment options for dogs with (non-metastatic) osteosarcoma and potentially for other cancers as well.…”
Section: Cellular Immunotherapy With Cytotoxic Lymphocytes (T – Cells and Nk -Cells)mentioning
confidence: 99%
“…Those are then ex vivo activated (using a proprietary formula) and expanded. The cell preparation is sent back to the veterinarian for infusion ( 11 ). An update on the study results were recently presented (Bryan, 2020, personal communication) 1 , and if the data hold, this could present a treatment options for dogs with (non-metastatic) osteosarcoma and potentially for other cancers as well.…”
Section: Cellular Immunotherapy With Cytotoxic Lymphocytes (T – Cells and Nk -Cells)mentioning
confidence: 99%
“…Therefore, we cannot deny the possibility that autologous lymphocyte therapy may be effective in preventing relapse in some human cancers [70,71], depending on how it is used. Furthermore, it was recently reported that the use of activated lymphocytes along with autologous tumor cell-derived vaccines after leg amputation in dogs with osteosarcoma not only prolonged survival but also resulted in complete remission of metastatic disease in one case [72].…”
Section: History Of Cancer Immunotherapy In Dogsmentioning
confidence: 99%
“…Schematic of cellular immunotherapies used in canine oncology trials. (1) autologous tumour vaccine followed by ex vivo activation and expansion of lymphocytes (Flesner et al 2020) 14 . (2) radiosensitisation prior to autologous NK cell infusion (Canter et al 2017) 15 .…”
Section: Adoptive Cell Transfermentioning
confidence: 99%
“…While TIL clinical trials are lacking in veterinary oncology, researchers associated with the University of Missouri and Elias Animal Health have used a novel approach to adoptive transfer using tumour reactive T cells 14 . Their clinical trial enrolled dogs with osteosarcoma and amputated their limbs, harvesting tumour tissue for the generation of an autologous tumour vaccine.…”
Section: Tumour Reactive T Cellsmentioning
confidence: 99%